2000
DOI: 10.1152/jappl.2000.89.2.799
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in the heat is limited by a critical internal temperature

Abstract: We examined whether fatigue during exertional heat stress occurred at a critical internal temperature independent of the initial temperature at the start of exercise. Microwaves (2.1 GHz; 100 mW/cm(2)) were used to rapidly (3-8 min) heat rats before treadmill exercise to exhaustion. In a repeated-measures design, food-restricted male Sprague-Dawley rats (n = 11) were preheated to three levels (low, medium, and high). In addition, two sham exposures, Sham 1 and Sham 2, were administered at the beginning and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(112 citation statements)
references
References 24 publications
(39 reference statements)
5
103
1
2
Order By: Relevance
“…For the ET, rats were given a 1-min warm-up running period at 20 cm/s. Treadmill speed was then increased to 30 cm/s on a 20°incline, and rats ran until exhaustion, which was defined as the inability of the rat to return to and maintain the pace of the treadmill for two continuous minutes (22,40,42,85). Time to exhaustion (s) was recorded.…”
Section: Animalsmentioning
confidence: 99%
“…For the ET, rats were given a 1-min warm-up running period at 20 cm/s. Treadmill speed was then increased to 30 cm/s on a 20°incline, and rats ran until exhaustion, which was defined as the inability of the rat to return to and maintain the pace of the treadmill for two continuous minutes (22,40,42,85). Time to exhaustion (s) was recorded.…”
Section: Animalsmentioning
confidence: 99%
“…The resulting DT co was thereby held to $1.0 8C. Walters et al [2000b] examined whether fatigue during exertional heat stress occurred at a critical T co independent of the initial T co at the start of exercise. Microwaves (2.1 GHz; 100 mW/cm 2 ) were used to rapidly (3-8 min) heat rats (n ¼ 11) to one of three levels before treadmill exercise to exhaustion.…”
Section: Intense or Prolonged Exposurementioning
confidence: 99%
“…The body's inability to control its increase in temperature (thermoregulatory failure), cardiovascular changes and changes in metabolic rate may also affect exercise capacity in a hot environment (17,23). It has been suggested that rather than dehydration, energy production or metabolic rate changes, absolute core temperature is the critical factor limiting exercise capacity in the heat (8,25). It is likely that when core temperature reaches critically high levels, an afferent signal is sent to the CNS, which responds by sending an efferent command to alter the neuromuscular recruitment strategy, to prevent cellular damage or rigor from occurring (19).…”
Section: Introductionmentioning
confidence: 99%